Fitness Center Business di Kabupaten Wonosobo (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
The problem in this study is how the conditions of fitness center business in Wonosobo regency. The aim of this study was to describe and assess the market and marketing aspects, technical and technological, organizational and management, and then economics and finance in every fitness center in Wonosobo regency. This study uses qualitative descriptive analysis. The research locations include four places, they are Gordon Gym, Happy Fitness, Jibril Fitness, and Fitness Mandala Putra with 17 people as the object. The meethods of collecting data that authors use, which is a combined method of participatory observation, interview and documentation. Conclusions from this research is the condition of the market and marketing aspects of the four average fitness center in good condition. Suggestions given to all managers and owners of fitness centers is concerned about the quality of service by increasing and improving human resources who are competent in the field of fitness. For instructors is expected to increase his knowledge about the world of fitness, for members and stakeholders supporting the development of fitness centers in Wonosobo regency.